Efficient whole-process carbon intensity calculation method for power users in active distribution networks - Shen, Zhiheng; Dan, Yangqing; Qi, Mengxue; Sun, Feifei; Sun, Yikai; Mei, Linjuehao (Frontiers in Energy Research, 2022)
With the tightening restrictions on carbon emission globally, the carbon intensity of the economic is receiving more attention than ever, but the results obtained by conventional methods are not accurate enough for the responsibility division. To change this situation, a power flow tracking method aimed at the distribution networks and an electricity-consumption-based carbon intensity calculation framework are proposed in this paper. Firstly, to overcome the obstacles created by the three-phase asymmetries and the scale expansion of the networks while processing power flow tracing, a phase-split calculation regime and a high-efficiency power flow tracing method are proposed, respectively. On that basis, a whole-process carbon intensity calculation framework is reported. By adding simplified models about industrial production processes, this paper gives the calculation route from the energy consumption to the carbon intensity for each user in the distribution network. Finally, we emulated with the IEEE 34 bus and 123 bus test feeders and analyze the numerical results, to prove the efficiency and effectiveness of the framework proposed.